(untitled) - Spilsbury, Louise (Oxford, 2010)
These motivating non-fiction readers are rich in content and beautifully illustrated. Fascinating information in carefully graded language appeals to a broad range of students and supports English across the curriculum, making the series perfect for CLIL (Content and Language Integrated Learning).
Keywords: Thuốc,English language,Medicine,Tiếng Anh; Văn học thiếu niên,Reading comprehension,Juvenile literature.,Đọc hiểu